Move Over, Descartes! Neuroscience Says You’re Wrong. - Kathleen Taylor; Catherine Marienau (Adult Education Research Conference, 2018)
Recent discoveries in neuroscience—“we feel, therefore we learn”—contradict Descartes’ rejection of the body’s role in thinking. This presentation examines implications for adult learning.
Keywords: neuroscience and adult learning; embodied learning; emotion and learning; analogical learning